Vegetation, soil, and weathered bedrock control hillslope rainfall-runoff processes on the Qinghai-Tibetan plateau - Pengfei Lin; Junjun Yang; Xi Zhu; Quanyan Tian; Zhibin He (CATENA, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

Profiling the spatial heterogeneity of microbiomes and volatilomes along internal environmental gradients in high-temperature Daqu - Guangdong Gan; Junjun He; Yong Yang; Lulu Song; Chun Pu; Chunlin Zhang (Food Bioscience, 2026)

Integrated chemometrics and untargeted metabolomics reveal the differential effects of drying methods on the quality of Sharen (Amomum villosum Lour.) - Zhixia Sun; Jun Chen; Junjun He; Ivan Shorstkii; Liqing Du; Taotao Dai; Yihui Wang; Yanli Yao; Chengmei Liu; Lizhen Deng (Food Bioscience, 2026)

Performance evaluation and mechanism analysis of different ice particle distribution shape parameter schemes in BCC-AGCM - Pengcheng Lin; Chunsong Lu; Yiming Liu; Xin He; Junjun Li; Tongwen Wu; Yixiong Lu (Atmospheric Research, 2026)

Improving Asian summer monsoon cloud and precipitation simulations through an ice crystal spectral relative dispersion parameterization - Xin He; Chunsong Lu; Jian Cao; Wentao Zhang; Hengqi Wang; Lei Zhu; Junjun Li; Xiaoqi Xu; Xiangjun Shi; Yuan Wang (Science China Earth Sciences, 2026)

Two-Dimensional Magnetotelluric Inversion Using Adaptive Mixed Lp Norm Regularization - Junjun Zhou; He Zhao; Zhidan Long; Ningbo Bai; Xiangyun Hu (Pure and Applied Geophysics, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Mechanisms of Drillability Enhancement and Damage Evolution in Granite Under Coupled Laser-Drill Interaction - Lei Yang; Mingzhong Gao; Bengao Yang; Jing Xie; Zhiqiang He; Junjun Liu; Fei Li; Xuemin Zhou; Kunchen He (Rock Mechanics and Rock Engineering, 2026)

A new and simple hypoplastic model for saturated soils reinforced by plant roots - Shusen Liu; Junjun Ni; Xudong Zhao; Yufeng Gao; Ning He; Yongfeng Deng (Computers and Geotechnics, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

Clinical Values of Serum Extracellular Vesicle MicroRNA Profiles as Molecular Biomarkers for Ischemic Stroke and Transient Ischemic Attack - Xinran Wu; Zhuoying Gu; Chenxi Kong; Xueqin Jiang; Qianqian He; Ziwu Han; Jia Wu; Junjun Wang (Molecular Neurobiology, 2026)

Red mud-modified biochar as an enhancer for solidification/stabilization of chromium(VI)-contaminated soil: Effects of pyrolysis temperature, feedstock, and dosage - Tao Chen; Bin He; Junjun Ni; Saif Ullah (Journal of Environmental Chemical Engineering, 2025)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Experimental and DEM investigation of root orientation effects on shear behavior of soils subjected to freeze–thaw cycles - Junjun Ni; Haoyu Zhang; Shusen Liu; Yongfeng Deng; Ning He (Engineering Geology, 2025)

Fast three-dimensional inversion of magnetotelluric data based on L-BFGS optimization - Ningbo Bai; Jiancheng Zhou; Xiangyun Hu; Bo Han; Junjun Zhou; Jian Yang; He Zhao (Journal of Applied Geophysics, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

The effect of stratus clouds on aerosol distribution in South China based on aircraft measurements - Jianqiu Gao; Zhujie Li; Junxia Li; Gang Wang; Chang Chen; Songwei He; Zhiyuan Shu; Shaoyu Hou; Junjun Lin (Atmospheric Research, 2025)

Mechanism and Feasibility Evaluation of Laser-Assisted Rock-Breaking in Drilling Fluid Environment - Xuemin Zhou; Mingzhong Gao; Junjun Liu; Lei Yang; Haichun Hao; Bengao Yang; Zhiqiang He; Xuan Wang (Rock Mechanics and Rock Engineering, 2025)

Coupling renewable energy with urban greening: quantifying the sustainable development potential of photovoltaic-green roofs - Taoyu Chen; Yantong Li; Yi Zhang; Hexu Ji; Xinyu Wang; Junjun He; Qunyue Liu; He Zhang (Sustainable Cities and Society, 2025)

Spatiotemporal diversification enables sustainable cotton-soybean production with enhanced yield and reduced emissions - Qingqing Lv; Ning He; Baojie Chi; Shizhen Xu; Zhenhuai Li; Li Wang; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Jianlong Dai; Junjun Nie; Yongjiang Zhang; et al. (Journal of Cleaner Production, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

An Adaptive Neural Network Fuzzy Sliding Mode Controller for Tracking Control of Deep-Sea Mining Vehicles - Shidong Wang; Zida Shan; Jialuan Xiao; Junjun Cao; He Zhang; Nan Sun (Journal of Marine Science and Engineering, 2025)
Traditional track-driven deep-sea nodule mining solutions significantly disrupt seabed ecosystems, making them unsuitable for commercial application. In contrast, ROV-like alternatives, such as the hovering mining vehicle, or HMV, offer substantial improvement in this regard and are deemed to be a viable way forward. This paper proposes an adaptive neural network fuzzy sliding mode controller architecture for the underwater trajectory tracking of HMV. The algorithm, named the Adaptive Radial Basis Function Neural Network Fuzzy Sliding Mode Controller (ARFSMC), replaces modeled vehicle dynamics with a radial basis function neural network (RBFNN). To enhance disturbance rejection, an adaptive mechanism is applied to the RBFNN output weighting matrix. Additionally, a fuzzy inference system (FIS) is implemented as the switching term, replacing the traditional signum function, to reduce high-frequency oscillations in the control signal. The stability of the algorithm under unknown external disturbance was confirmed via Lyapunov stability analysis. To validate the ARFSMC’s performance, three numerical simulation cases were conducted, each designed to reflect an expected operation scenario of the HMV, through which the tracking performance of the ARFSMC under time-varying system inertia is validated and benchmarked against conventional sliding mode control (CSMC) and double-loop sliding mode control (DSMC). The simulation results confirm that comparing the above two controllers, the root mean square error (RMSE) of the ARFSMC is reduced by 15.0% and 11.4%, respectively. And when comparing the CSMC, the chattering is reduced by 97.8%. Both indicate their high robustness and superior performance in tracking control. The controller development and numerical validation in this work are aimed at the trajectory tracking challenge of the HMV in deep-sea mining operation. The dynamical modeling of the vehicle is based on parameters of the HaiMa ROV. External disturbance from currents were considered as sinusoidal functions modified with random noise.

Effects of chitosan on restoring spermatogenesis in mice: Insights from gut microbiota and multi-omics analysis - Guitian He; Boqi Zhang; Tong Chen; Caomeihui Shen; Nan Wang; Junjun Yang; Fuqiang Chang; Yue Sui; Xuanqi Yin; Yueying Wang; Sihui Wang; Yaqiu Li; et al. (Food Research International, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Hydrodynamic characteristics and internal flow field of a perforated fishing vessel under wave conditions - Xi Zhang; Junjun Lv; Dachuan He; Ke Wang; Ying Liu; Jie Zhi (Ocean Engineering, 2024)

The spatiotemporal heterogeneity of microbial community assembly during pit fermentation of soy sauce flavor baijiu - Liang Yang; Xiaodong Huang; Jiafeng Hu; Hong Deng; Junjun He; Chunlin Zhang (Food Bioscience, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Uncertainty of canopy interception modeling in high-altitude Picea crassifolia forests of Semi-arid regions - Junjun Yang; Zhibin He; Pengfei Lin; Jun Du; Dong Shi; Meng Bai (Agricultural and Forest Meteorology, 2024)

Temperature sensitivity of aerobic and anaerobic organic carbon mineralization varies with climate and soil depth in riparian zones - Mingzhu Lu; Gang He; Lei Fan; Guihua Liu; Junjun Wu; Wenzhi Liu; Lin Ma (Soil Biology and Biochemistry, 2024)

The hydrodynamic study of the interaction between waves and objects in permeable reef environment - Xi Zhang; Junjun Lv; Runnan Hui; Dachuan He; Ke Wang (Ocean Engineering, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Catalytic activation of persulfate by nanoscale zero-valent iron-derived supported boron-doped porous carbon for bisphenol A degradation - Fuxiang Du; Xiaowei Huo; Chao Xue; Chenggui Zhang; Huichao Wang; Chao Dai; Yang Yang; Cheng Lai; Junjun He (Environmental Science and Pollution Research, 2024)

Nitrogen-rich penicillin residue biochar for activation of peroxymonosulfate for an efficient degradation of tetracycline and its dual-pathway mechanism - Jianrui Niu; Hua Jia; Minghao Yu; Jinyu Zhu; Junjun Ma; Zhuang He; Weizhang Zhong; Yongjiang Hou; Yankai Guo (Process Safety and Environmental Protection, 2024)

Response of growth performance and cecum microbial community to cyclic heat stress in broilers - Junjun Yuan; Yan Li; Shiang Sun; Jiaying Wu; Jin Zhou; Shaojun He (Tropical Animal Health and Production, 2024)

The Probability Density Function Related to Shallow Cumulus Entrainment Rate and Its Influencing Factors in a Large-Eddy Simulation - Lei Zhu; Chunsong Lu; Xiaoqi Xu; Xin He; Junjun Li; Shi Luo; Yuan Wang; Fan Wang (Advances in Atmospheric Sciences, 2024)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

Computational identification and systematic classification of cytochrome P450 genes in Pogostemon cablin provide insights into flavonoids biosynthesis - Junjun Li; Cao Deng; Mengjia Liu; Yang He (Acta Physiologiae Plantarum, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Field investigation and numerical modelling of gas extraction in a heterogeneous landfill with high leachate level - Haijian Xie; Shuangke Fei; Haijie He; An Zhang; Junjun Ni; Yun Chen (Environmental Science and Pollution Research, 2022)

How does the urban–rural income gap affect regional environmental pollution?——Re-examination based on the experience of cities at prefecture level and above in China - Weiwei He; Junjun Hou; Keke Cheng (Environmental Science and Pollution Research, 2022)

Sevoflurane-Induced Neurotoxicity in the Developing Hippocampus via HIPK2/AKT/mTOR Signaling - Lirong Liang; Ze Fan; Danyi He; Youyi Zhao; Tian Zeng; Bing Liu; Tianyuan Ma; Junjun Kang; Hui Zhang (Neurotoxicity Research, 2022)

Geochemical characteristics and source of crude oil in the Shenhu uplift, Pearl River Mouth Basin, South China Sea - Xiaoyan Fu; Shijia Chen; Xin He; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Spatial relationship between climatic diversity and biodiversity conservation value - Junjun Wang; Ruidong Wu; Daming He; Feiling Yang; Peijun Hu; Shiwei Lin; Wei Wu; Yixin Diao; Yang Guo (Conservation Biology, 2018)
Capturing the full range of climatic diversity in a reserve network is expected to improve the resilience of biodiversity to climate change. Therefore, a study on systematic conservation planning for climatic diversity that explicitly or implicitly hypothesizes that regions with higher climatic diversity support greater biodiversity is needed. However, little is known about the extent and generality of this hypothesis. We used the case of Yunnan, southwest China, to quantitatively classify climatic units and modeled 4 climatic diversity indicators, including the variety (VCU), rarity (RCU), endemism (ECU) of climatic units, and a composite index of climatic diversity (CICD). We used 5 schemes that reliably identify priority conservation areas (PCAs) to identify areas with high biodiversity conservation value. We then investigated the spatial relationships between the 4 climatic diversity indicators and the results of the 5 PCA schemes and assessed the representation of climatic diversity within the existing nature reserves. The CICD was the best indicator of areas with high conservation value, followed by ECU and RCU. Contrary to conventional knowledge, VCU was not positively associated with biodiversity conservation value. The rarer or more endemic climatic units tended to have higher reserve coverage than the more common units. However, only 28 units, covering 10.5% of the land in Yunnan, had >17% of their areas protected. In addition to climatic factors, topography and human disturbances also significantly affected the relationship between climatic diversity and biodiversity conservation value. Our results suggest that climatic diversity can be an effective surrogate for establishing a more robust reserve network under climate change in Yunnan. Our study improves understanding of the relationship between climatic diversity and biodiversity and helps build an evidence‐based foundation for systematic conservation planning that targets climatic diversity in response to climate change.

Integrating lidar with Landsat data for subalpine temperate forest aboveground carbon estimation - Jun Du; Zhibin He; Longfei Chen; Junjun Yang; Xi Zhu; Weijun Zhao (International Journal of Remote Sensing, 2015)

Detecting the effects of climate change on canopy phenology in coniferous forests in semi-arid mountain regions of China - Jun Du; Zhibin He; Junjun Yang; Longfei Chen; Xi Zhu (International Journal of Remote Sensing, 2014)

Exogenous EDDS modifies copper-induced various toxic responses in rice - Junjun Tan; Shibin He; Shihan Yan; Yingnan Li; Hui Li; Hao Zhang; Lin Zhao; Lijia Li (Protoplasma, 2014)

Distribution of MICB diversity in the Zhejiang Han population: PCR sequence-based typing for exons 2–6 and identification of five novel MICB alleles - Yanling Ying; Yanmin He; Sudan Tao; Zhedong Han; Wei Wang; Nanying Chen; Junjun He; Wei Zhang; Ji He; Faming Zhu; Hangjun Lv (Immunogenetics, 2013)